2015
DOI: 10.1111/sode.12168
|View full text |Cite
|
Sign up to set email alerts
|

Making Amends: Children's Expectations about and Responses to Apologies

Abstract: Two studies investigate children's expectations and actual responses to a transgressor's attempt to make amends. In Study 1, six‐ and seven‐year‐olds (N = 16) participated in a building activity and then imagined how they would respond if a transgressor knocked over their tower and then apologized spontaneously, apologized after prompting, offered restitution, or did nothing. Children forecasted that they would feel better and would share more when a transgressor offered restitution or apologized spontaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Unlike previous research that has typically placed children in the role of bystanders, where children can reason in a relatively “cool” cognitive state (e.g., Darby & Schlenker, , ; Smith et al., ; Vaish et al., ), our findings demonstrate that even as victims, when children may experience stronger emotions such as sadness and anger, 4‐ to 5‐year‐olds show sensitivity to remorse and are more forgiving of remorseful transgressors. Moreover, in the few prior studies in which children were the victims, they responded to explicit apologies, which are conventional cues of remorse that children are trained from early on to use and expect (Drell & Jaswal, ; Smith & Harris, ; Smith et al., ); our findings demonstrate that by at least 5 years of age, children forgive transgressors who display remorse even in the absence of explicit apologies (see also Vaish et al., ). Transgressors’ remorse is thus a powerful elicitor of forgiveness, even in young children.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Unlike previous research that has typically placed children in the role of bystanders, where children can reason in a relatively “cool” cognitive state (e.g., Darby & Schlenker, , ; Smith et al., ; Vaish et al., ), our findings demonstrate that even as victims, when children may experience stronger emotions such as sadness and anger, 4‐ to 5‐year‐olds show sensitivity to remorse and are more forgiving of remorseful transgressors. Moreover, in the few prior studies in which children were the victims, they responded to explicit apologies, which are conventional cues of remorse that children are trained from early on to use and expect (Drell & Jaswal, ; Smith & Harris, ; Smith et al., ); our findings demonstrate that by at least 5 years of age, children forgive transgressors who display remorse even in the absence of explicit apologies (see also Vaish et al., ). Transgressors’ remorse is thus a powerful elicitor of forgiveness, even in young children.…”
Section: Discussionsupporting
confidence: 61%
“…Nonetheless, it will be important for future research to move away from forced-choice to single transgressor scenarios and assess how children respond when the direct contrast between remorseful and unremorseful transgressors is absent. Based on prior work (e.g., Drell & Jaswal, 2016;Smith & Harris, 2012), we would expect our findings to hold with such paradigms as well.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Our research shed light on how children think about the emotions associated with lying and confessing, but little is known about how children actually feel after offering lies and confessions. Affective forecasting paradigms (e.g., Gilbert, Lieberman, Morewedge, & Wilson, 2004) have demonstrated that people often make errors in predicting how they will actually feel about a focal event, and recent research indicates that children may incorrectly anticipate the emotions that stem from receiving an apology (Drell & Jaswal, 2015). Thus, it is possible that although young children predict negative feelings following a confession, they may actually experience positive emotions; likewise, it is also possible that older children’s more positive predictions are inaccurate.…”
Section: Discussionmentioning
confidence: 99%
“…Here, again, some work has assessed children’s responses to explicit apologies. After suffering minor transgressions, 4- to 7-year-olds who receive an apology report improved feelings, evaluate the transgressor more positively, and act more prosocially towards the transgressor than children who receive no apology (Drell & Jaswal, 2016; C. E. Smith & Harris, 2012).…”
Section: Guilt: Repairing Prosocial Relationshipsmentioning
confidence: 99%